Double-Lumen Tubes and Auto–PEEP During One-Lung Ventilation. Issue 5 (October 2016) - Spaeth, J.; Ott, M.; Karzai, W.; Grimm, A.; Wirth, S.; Schumann, S.; Loop, T.
Abstract : (Abstracted from Br J Anaesth, 116(1):122–130, 2016) One-lung ventilation (OLV), which is routinely facilitated by double-lumen tubes (DLTs) during thoracic anesthesia, certainly is not without its challenges. In an effort to reduce the incidence of progressive lung hyperinflation, precipitated by an unintended increase in positive end-expiratory pressure (auto-PEEP) during such procedures, researchers set about studying the impact of adult-sized DLTs on dynamic auto-PEEP during OLV.